Oral Exam System at Teacher Appointments in Turkey - Ismail Colak; Selcuk Besir Demir (Institute of Advanced Engineering and Science, 2017)
Oral Exam system is applied all over the world, is recently applied in Turkey. After teacher candidates pass the PESE (General Knowledge, General Skills, Educational Sciences, and TPFK), they receive Oral Exam, and they are appointed with the points they receive from this stage or they are considered as unsuccessful. In other words, while Oral Exams are used as the complementary elements of written and similar other exams in the world, they are used as the sole determinants of appointing teachers in Turkey, which is beyond being complementary. As a matter of fact, in countries where Oral Exams are applied, it is observed that this system is used sometimes for preferential purposes, and the influence of Oral Exams on appointment point is kept low. Another reason for the criticisms of the educational syndicates that are active in Turkey on Oral Exam application is the suspicion of its activating the “preferential treatment” mechanism, because evaluations have subjectivity in them; and the evaluations of the members of the commission about the answers of the candidates are not based on adequate and concrete data